Certifying improvement, improving certification: An analysis based on the artisanal and small-scale mining sector - Miriam Bodenheimer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
There are a plethora of voluntary initiatives indirectly connected to artisanal and small-scale mining (ASM), but until recently, none of these standards were explicitly concerned with ASM. It is only with the introduction of certification schemes specific to the ASM sector that guidelines are being designed and implemented that expressly address its unique dynamics. But implementing certification schemes remains costly and it is therefore important to analyze in detail to what degree problems within the ASM sector can be addressed through these mechanisms before making more of those investments. Consequently, this paper aims to perform such an evaluation through a two-pronged approach consisting of a theory-based analysis of the working mechanisms of certification and a review of qualitative data from interviews with key players in the field of ASM certification. The results show that there are still a number of problems in how small-scale mines are being certified, but that, at the same time, the approach has the potential to make significant contributions to development and poverty-reduction in the sector. The paper concludes with recommendations based on these findings.
urn:nbn:de:0011-n-3070075
Keywords: 330